Awareness Among Dairy Farmers Regarding Breeding and Health Practices in Una and Hoshiarpur - Singh, Ravdeep; Kumar Sharma, Rakesh; Singh, Jaswinder; Kasrija, Rajesh; Deshmukh, Bharti; Hon parkhe, Mrigank (The Indian Journal of Animal Reproduction, 2025)
This study was conducted to assess and compare the awareness and adoption of reproductive and healthcare manage ment practices among dairy farmers in Hoshiarpur district of Punjab and Una district of Himachal Pradesh. A total of 80 respondents (40 from each district) were selected using a purposive random sampling method. Data were collected through a pre-tested structured interview schedule and analysed using descriptive statistics and t-tests to determine the significance of observed differences.The results revealed significant regional disparities in both awareness and adoption of recommended dairy practices. Farmers from Hoshiarpur consistently reported higher mean scores across most indi cators. In reproductive and breeding management, significant differences (p < 0.05) were observed in farmers’ knowledge regarding the importance of age at first insemination (Hoshiarpur: M = 0.90 ± 0.04; Una: M = 0.70 ± 0.07), preference for artificial insemination over natural service (0.82 ± 0.06 vs. 0.62 ± 0.07), awareness of heat detection (0.82 ± 0.06 vs. 0.60 ± 0.07), semen quality (0.75 ± 0.06 vs. 0.52 ± 0.07) and use of veterinary help during parturition (0.82 ± 0.06 vs. 0.57 ± 0.07). In terms of healthcare practices, significant differences were found in seasonal vaccination awareness (0.95 ± 0.03 vs. 0.80 ± 0.06) and application of prophylactic measures against contagious diseases (0.32 ± 0.07 vs. 0.12 ± 0.05).The overall mean adoption score was significantly higher in Hoshiarpur (0.68 ± 0.05) than Una (0.53 ± 0.06), indicating more effective extension and veterinary service delivery in Punjab. These findings emphasize the need for focused awareness programs, improved service infrastructure and targeted interventions in Una district to enhance reproductive efficiency and health management in dairy farming.